2017
DOI: 10.22159/ajpcr.2017.v10i4.16194
|View full text |Cite
|
Sign up to set email alerts
|

Colorectal Cancer and Its Risk Factors Among Patients Attending a Tertiary Care Hospital in Southern Karnataka, India

Abstract: Objective: The objective of this study is to determine the association between certain sociodemographic and lifestyle factors with colorectal cancer.Methods: This case-control study was conducted using a pre-designed questionnaire among 100 incident colorectal cancer patients and 200 unmatched controls attending a Tertiary Care Hospital in Southern Karnataka. Cases and the controls were interviewed, and details regarding their sociodemographic factors were collected. Information on lifestyle factors such as di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…Colorectal cancer: Three studies (one pooled cohort 63 one cohort 64 , and one case-control 65 ) were retrieved evaluating risk of colorectal cancer in SLT users. Of these, only one study with pooled cohort reported a significantly higher risk of rectal cancer in snus users.…”
Section: Resultsmentioning
confidence: 99%
“…Colorectal cancer: Three studies (one pooled cohort 63 one cohort 64 , and one case-control 65 ) were retrieved evaluating risk of colorectal cancer in SLT users. Of these, only one study with pooled cohort reported a significantly higher risk of rectal cancer in snus users.…”
Section: Resultsmentioning
confidence: 99%
“…PD-1 targets the receptor or tumor cells and prevents the tumor cells from hiding from the immune system. Pemprolizumab is used to treat metastatic bowel cancers that have the molecular property of MSI-H or dMMR [54][55][56].…”
Section: Pemprolizumabmentioning
confidence: 99%
“…Colorectal cancer (CRC) is one of the most common solid cancer affecting both sexes nearly 10% of total cancer cases [1,2]. In Egypt, CRC occupies first rank among digestive system malignancies and fifth rank among total cancers [3].…”
Section: Introductionmentioning
confidence: 99%